Mitochondrial stroke-like episodes: The search for new therapies - Daniele Orsucci; Elena Caldarazzo Ienco; Vincenzo Montano; Gabriele Siciliano; Michelangelo Mancuso (Elsevier, 2022)
A mitochondrial stroke-like event is an evolving subacute neurological syndrome linked to seizure activity and focal metabolic brain derangement in a genetically determined mitochondrial disorder. The acronym "MELAS" (mitochondrial encephalopathy associated with lactic acidosis and stroke-like lesions) identifies subjects with molecular, biochemical and/or histological evidence of mitochondrial disorder who experience stroke-like lesions. MELAS is a rare inherited mitochondrial disease linked to severe multiorgan involvement and stress-induced episodes of metabolic decompensation and lactic acidosis. Unfortunately, there are no etiopathogenetic therapies for stroke-like episodes to date, and the treatment is mainly based on anti-epileptic drugs and supportive therapies. This perspective opinion article discusses the current care standards for MELAS patients and revises current and innovative emerging therapies for mitochondrial stroke-like episodes.